THE CORRELATION BETWEEN STUDENTS’ LINGUISTIC INTELLIGENCE AND READING COMPREHENSION - aulia nugraheni; n. nuardi (Indonesian Journal of Integrated English Language Teaching, 2018)
This research aimed at determining the correlation between students’ linguistic intelligence and reading comprehension. There were two variables used in this research. The first was linguistic intelligence and the second was reading comprehension. The subject of this research was the eighth grade students at Islamic Junior High School Darul Qur’an Tarai Bangun Kampar Regency whereas the object of this research was the correlation between students’ linguistic intelligence and reading comprehension. The population of this research was 55 students. To choose the sample, the researcher used total sampling technique. In collecting the data, the researcher used questionnaire for students’ linguistic intelligence and test for reading comprehension. From the data analysis which had been done by using SPSS 16 version, it could be shown that the sig. (2-tailed) value was 0.000, smaller than the significant alpha 0.05 (sig.t < 0.05). It means that null hypothesis (Ho) was rejected while the alternative hypothesis (Ha) was accepted. The value of correlation coefficient (r) was 0.676. In conclusion, there was a significant positive correlation between students’ linguistic intelligence and reading comprehension. The researcher also found that 46% of linguistic intelligence can influence reading comprehension.